A Standards-Based Digital Twin of an Experiment with a Scale Model Ship. (April 2022) - Fonseca, Ícaro Aragão; Gaspar, Henrique Murilo; de Mello, Pedro Cardozo; Sasaki, Humberto Akira Uehara
Abstract: We propose the use of existing data standards and web technologies to modeling and development of digital twin ships. Our research provides an open framework that can be linked to services such as visualizations, simulations and remote control. The case study applies the standards-based framework to an experiment that involved a scale model ship equipped with a dynamic positioning system under artificial waves. The digital twin prototype illustrated the capability of mirroring and controlling the model's position in real-time, and predicting motion responses across wave conditions via a web application. Thus, it closes the loop between test and design in the life cycle by allowing validation of results in comparison to empirical data during operation. The results from these experiments are used to discuss an expanded version of the digital twin for validation and optimization of motion response, as well as its implications to the system's (ship) taxonomy and data management. The conclusion summarizes lessons when using the adopted standards, as well as challenges when scaling the approach to real life operations. Future research is proposed toward extending the standardization to more complex cases. Highlights: Open and standards-based development of a digital twin for a dynamic positioning experiment in a wave basin. The digital twin monitors wave motion response and controls dynamic positioning in real-time. The data organization follows a function-oriented taxonomy based on the Vessel Information System, created by DNV. Among the standards used are JSON for metadata, glTF for visualization and ISO 19848 for data logs. Simulation interface is developed as a Web-app for wider compatibility across devices and remote access over the internet.